Psychometric properties of Persian version of wound-QOL questionnaire among older adults suffering from chronic wounds - Savadkoohi, Hamed; Barasteh, Salman; Ebadi, Abbas; Ashrafizadeh, Hadis; Akbarzadeh Amirdehi, Mahdi; Safdari, Ali; Mollahadi, Mohsen; Oghli, Saeid Hossein (Frontiers in Psychology, 2023)
Background: Patients with chronic wounds experience various biopsychosocial problems which severely affects their quality of life. Thus, a Persian instrument to assess the quality of life of these patients is required. This study aimed to determine the psychometric properties of the Persian version of the wound-QOL questionnaire. Methods: This methodological study was performed on Iranian patients during 2021-2022. The translation was carried out via forward-backward method. Face validity was addressed with 10 patients and content validity with 12 wound specialists. Construct validity was also assessed by performing exploratory factor analysis (n = 100) and convergent validation with EQ-5D-3L plus Pain VAS Score and known-groups validity. The reliability was assessed by internal consistency using Cronbach’s alpha coefficient and test-retest. Results: A total of 100 patients with chronic wounds were included in the study. Two factors with cumulative variance of 65.39% were extracted during exploratory factor analysis (EFA). The results revealed a significant and high correlation between the total scores of wound-QOL questionnaire, the Persian version of EQ-5D-3L (P = 0.000, r = 0.502), and Pain score (0–10) (P = 0.000, r = 0.627). The Cronbach’s alpha was 0.743 and stability of the questionnaire (α = 0.872) was confirmed. In confirming the known-groups validity, the results showed that this tool can differentiate the QOL of patients with different wounds. Conclusion: The Persian version of the wound-QOL questionnaire is a valid and reliable questionnaire which can measure the quality of life of patients with chronic wounds. This instrument can be used in clinical evaluation as well as research purposes across the Iranian population.